(untitled) (Research, Society and Development, 2021)
Goal: Describe the profile of continuous medical treatment in oncologic patient assisted in a CACON. Method: A Cross-sectional study, analytical and quantitative. The sample is constituted by patients diagnosed with cancer, inserted to begin oncologic treatment at the High Complexity Center (CACON), evaluated in the period of August, 2018 and January, 2019. Results: Two hundred seventy patients participated in the research, fifty- three percent were of female gender and fifty-one point one percent over sixty years old. It was found asssociation between the use of the medicament and: female sex (p=0.025); be married or have a companion (p=0.049); and over sixty years old (p=0.000). The most used medicament group by oncologic patients in treatment with continuous medicine was the cardiovascular system (69.56%). It was verified the association between using continuous medicine and self-reporting of: hypertension (p=0.000); diabetes mellitus (p=0.013); acute myocardial infarction (p=0.045); depression (p=0.001) and alcoholic drinks (p=0.000). Conclusion: It is important to know the treatment profile of the continuous medicine users in oncologic treatment to ensure the patients safety and the effectiveness of the treatment.